Upaya Unicef dalam Mendifusikan Norma Anti Perkawinan Anak di indonesia Tahun 2018-2020 - tamba, agnes newitha; Wiranata, I Made Anom; Priadarsini, Ni Wayan Rainy (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2023)
This thesis discusses Unicef's efforts to diffuse anti-child marriage norms in Indonesia with the aim of reducing the number of child marriage cases in Indonesia in 2018-2020. Child marriage is a form of violation of human rights, especially the rights of children. The existence of child marriage in Indonesia is driven by several factors, namely: economy, culture, family upbringing and also place of residence. Based on UNICEF data, Indonesia is one of the countries that has the number 8 case rate of child marriage in the world. Due to the rise of cases of child marriage in Indonesia, Unicef ??is an international organization that moves to uphold the rights of children and women to deal with cases of child marriage by running work programs and collaborating with the Indonesian government. This thesis aims to find out what efforts have been made by Unicef ??in handling cases of child marriage in Indonesia in 2018-2020. The conceptual framework used in this research is the International Organization and the Diffusion of Anti-Child Marriage.